Effect of Temperature on the Adsorption of Organic Vapours on Activated Carbon Fibres - Zheng-Hong Huang; Feiyu Kang; Jiming Hao (Adsorption Science & Technology)
Viscose rayon-based activated carbon fibre (ACF) was prepared by CO 2 activation and the pore structure of all samples characterized via nitrogen adsorption at −196°C. The influence of temperature on the adsorption of organic vapour onto ACF was studied by gravimetric methods. The results showed that the adsorption capacity towards organic vapour decreased with increasing temperature at a given concentration. The larger the specific surface area of the ACF, the greater the extent to which its vapour adsorption performance was affected by temperature. It is suggested that an ACF of a relatively low burn-off would be suitable for adsorption at higher temperatures.